2022
DOI: 10.3390/horticulturae8040334
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Seed and Leaf Treatment with Ascorbic Acid Extends the Planting Period by Improving Tolerance to Late Sowing Influences in Parsley

Abstract: Abnormal production of reactive oxygen species (ROS) is an undesirable event which occurs in plants due to stress. To meet this event, plants synthesize ROS-neutralizing compounds, including the non-enzymatic oxidant scavenger known as vitamin C: ascorbic acid (AsA). In addition to scavenging ROS, AsA modulates many vital functions in stressed or non-stressed plants. Thus, two-season (2018/2019 and 2019/2020) trials were conducted to study the effect of integrative treatment (seed soaking + foliar spray) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The major vital components of the BHS have previously been used individually as foliar applications with success supporting plant performance and increasing its resistance to stress, e.g., organic acids [ 63 ], soluble sugars [ 64 , 65 ], amino acids [ 66 , 67 , 68 ], proline [ 66 , 69 ], essential nutrients [ 70 , 71 , 72 ], ascorbate [ 73 ], B-group vitamins [ 74 , 75 ], selenium [ 7 ], and iodine [ 76 ]. In this paper, all of these components are combined into a solution (BHS) in organic forms, giving this solution a multi-mechanism for plants to adjust to stress conditions and resist stress via signaling pathways and efficient mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The major vital components of the BHS have previously been used individually as foliar applications with success supporting plant performance and increasing its resistance to stress, e.g., organic acids [ 63 ], soluble sugars [ 64 , 65 ], amino acids [ 66 , 67 , 68 ], proline [ 66 , 69 ], essential nutrients [ 70 , 71 , 72 ], ascorbate [ 73 ], B-group vitamins [ 74 , 75 ], selenium [ 7 ], and iodine [ 76 ]. In this paper, all of these components are combined into a solution (BHS) in organic forms, giving this solution a multi-mechanism for plants to adjust to stress conditions and resist stress via signaling pathways and efficient mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that spraying C increased the activity of the enzyme with increasing spraying concentrations on the vegetative part of corn. The spraying concentrations 100 and 200 mg.l -1 gave an average of 48.91 and 51.74 U. min.g -1 fw sequentially compared to the control treatment, which gave the lowest average 43.80 U.min.g -1 fw, and this is due to the role, of vitamin C as an important non-enzymatic antioxidant in stimulating the effectiveness of antioxidant enzymes, including the peroxidase enzyme [43] especially with a significant correlation relationship in the increase in peroxidase activity with an increase in the presence of C ‫؛‬ because the latter is a cofactor for oxidation enzymes oxygenase and hydrogenase enzymes, and peroxidase enzyme is a part of which [44] these results agree with [23]. The statistical data in table (4) also showed that the two levels of exposing the seedlings to heat had a significant effect on increasing the activity and activity of the peroxidase enzyme.…”
Section: Catalase ( Unit Minute G -1 Fresh Weight )mentioning
confidence: 91%
“…Ascorbic acid treatment leads to an increase in photosynthetic pigments, which can be attributed to its function in photosynthesis as a substitute electron donor for PSII in abiotic stress conditions. It also protects the photosynthetic apparatus in chloroplasts by reducing ROS activity (Venkatesh and Park, 2014), improving absorption of essential elements, particularly iron, magnesium, potassium, nitrogen, and other cations (Al-Taweel et al, 2022), which are essential for the activation of enzymes and the formation of both chloroplasts and chlorophyll. Furthermore, ascorbic acid is essential for scavenging harmful ROS produced as byproducts of photosynthesis and is a fundamental element of excess photonic energy dissipation mechanisms like the xanthophyll cycle (Yabuta et al, 2007) and the water-water cycle (Neubauer and Yamamoto, 1992;Asada, 2006).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…These results are consistent with those of Elkelish et al (2020), who reported that exogenous ascorbic acid administration can enhance the endogenous ascorbic acid concentration under various stress conditions, hence increasing plant tolerance to a variety of stresses. Al-Taweel et al (2022) discovered that applying 2.0 mM ascorbic acid for integrative (seed soaking + foliar spraying) significantly enhanced the contents of nutrients, soluble sugars, free proline, and ascorbic acid, as well as growth, yields, and essential oil fractions in parsley plants. It was also more successful in giving parsley plants a higher degree of resistance to unfavorable circumstances.…”
Section: Yield Qualitymentioning
confidence: 99%
See 1 more Smart Citation